Anmerkungen zu Rainer Vossen's Besprechung meines Buches: The Nominal and Verbal Afformatives of Nilo-Hamitic and Hamito-Semitic, with some phonetic observations and a new vocabulary. Wiesbaden 1975 (AKM. 42,2.) in: Kratylos 22 (1979) - Hohenberger, Johannes
ersch. 1981.